2006
DOI: 10.2106/jbjs.e.01288
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Rotation on Cutting of the Tibia in Total Knee Arthroplasty

Abstract: When an extramedullary alignment guide is used to prepare the tibia in total knee arthroplasty, varus alignment of the tibial component can occur because of a rotational mismatch between the proximal part of the tibia and the ankle joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…2, 3). All measurements were performed using image-analysis software (Real INTAGE, Tokyo, Japan) [23,24]. The axial images for every vertebra were obtained as follows.…”
Section: Methodsmentioning
confidence: 99%
“…2, 3). All measurements were performed using image-analysis software (Real INTAGE, Tokyo, Japan) [23,24]. The axial images for every vertebra were obtained as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The factors that influence the onset and progression of osteoarthritis are not well understood, although it is known that lower extremity mal-alignment is related to joint problems [2,[5][6][7][8][9]. We found that many patients complained of pain in the ankle after total knee arthroplasty, and we surmised that a change in the alignment of the lower extremity caused by a relatively large knee varus correction angle might be one of the reasons for the discomfort.…”
Section: Resultsmentioning
confidence: 94%
“…Many authors173031 have reported variability in the identification of the transepicondylar axis. We have used the medial sulcus for the medial landmark in this study.…”
Section: Discussionmentioning
confidence: 99%